Retained Surgical Sponges after Craniotomies: Imaging Appearances and Complications - Kim, A.K.; Lee, E.B.; Bagley, L.J.; Loevner, L.A. (American Journal of Neuroradiology, 2009)
SUMMARY: Imaging within 24 to 48 hours after most neurosurgical procedures is a routine practice. Nonresorbable surgical sponges have radiopaque filaments readily visible on CT scans and plain film radiographs. However, the proton-poor barium sulfate responsible for this radio-opacity is generally not detectable on MR imaging in the immediate post-operative period. Findings on MR imaging become more evident with elapsing time and when a foreign-body reaction to the sponge manifests as a mass lesion, which can mimic residual or recurrent intracranial tumor or abscess. Although preventive measures by our surgical colleagues to ensure accurate and correct sponge counts before and after wound closure is paramount, even the most fastidious efforts may rarely result in an inadvertently retained surgical sponge. The role of the radiologist is to recognize the imaging findings of this entity and its potential complications so that appropriate and prompt management can be initiated.